Elimination of Giardia muris in naturally infected murine experimental model: Complementary treatment (Research, Society and Development, 2021)
Objective: This study proposed a complementary treatment for murine giardiasis comparing Black tea (CPR) (Camellia sinensis) with Metronidazole (MT), Fembendazole (FB) and Metronidazole in association with Sulfadimetoxin (Mts) in male Swiss mice (30) divided into six groups (CPR, MT, FB/MT, Mts, CPR/Mts and Untreated Control - C+) with five animals each. Methodology: The treatment was intragastric, for 7 days 1x/day and group C+ received only water. The experiments were conducted blindly, controlled, randomized, and repeated once with same number of animals. Clinical parameters (weight, water consumption, feed and excreta elimination) were also evaluated. Results: The animals in the CPR/MtS and MtS groups and in the CPR group presented negative parasitological and molecular results for G. muris on the 5th and 7th day after starting treatment, respectively. The animals in groups FB/MT, MT and C+ continued to eliminate cysts after the end of treatment.  The animals of group C+ presented significant weight loss in relation to the animals of the other groups and consumed less feed (p=0.0001) in relation to the animals of groups CPR/MtS, FB/MT and MT. Conclusion: The complementary treatment with black tea alone or associated with MtS was effective to eliminate G. muris, being a promising strategy for murine experimental model. The untreated animals that maintained high parasite load showed significant changes in clinical parameters, showing the importance of eliminating pre-existing infection and increasing the reliability of the results of experiments using these animals.